(untitled) (Revista Argentina de Cirugía, 2021)
Background: currently a discussed point of laparoscopic cholecystectomy (LC) is the systematic implementation of intraoperative cholangiography (IOC); however, it allows the diagnosis of unsuspected common bile duct stones (UBDS). Objective: to establish the percentage of IOC performed, the number of UBDS diagnosed, to describe what therapeutic was used to solve them and to establish if there is a relationship between the size of the diagnostic lithiasis and the transcystic treatment of the same. Results: of the 1077 elective LC, IOC could be performed in 89.14% of patients. In 2014 the percentage of IOC was the highest in the series (95.38%). 38 UBDS were found. The treatment included the transcritical approach and intraoperative ERCP. Overall morbidity was 7.9% without mortality. Discussion: our IOC percentage is below the utterance in other publications, but the percentage has increased over the years. The incidence of UBDS in our case was 3.96%. In our service we first try the transcritical resolution (success rate of 77.42% without complications). Another option is intraoperative ERCP that was used in 4 cases with 100% efficacy without complications. Conclusion: the treatment of the UBDS continues being a challenge for the surgeons, mainly due to the unpredictability of the picture; a very important factor for transcystic resolution is the size of the stone found (more or less than 6 mm). We consider intraoperative ERCP as an important tool in the resolution of this pathology.